Hydraulic fracturing - Smith, Michael Berry; Montgomery, Carl T. (CRC Press, Taylor & Francis Group, 2015)
Hydraulic Fracturing effectively busts the myths associated with hydraulic fracturing. It explains how to properly engineer and optimize a hydraulically fractured well by selecting the right materials, evaluating the economic benefits of the project, and ensuring the safety and success of the people, environment, and equipment. From data estimation to design, operation, and performance management, the text presents a logical, step-by-step process for hydraulic fracturing that aids in proper engineering decision making when stimulating a particular reservoir. Numerous problem sets reinforce the.
Keywords: Hydraulic fracturing.; Petroleum engineering.; elektronické knihy; electronic books